Analisis Faktor-Faktor yang Memengaruhi Status Kemiskinan Ekstrem Rumah Tangga di Provinsi Maluku Tahun 2021 - Faujan, La Ode; Agustina, Neli (Politeknik Statistika STIS, 2023)
Extreme poverty is a global issue contained in SDG's first goal. Indonesia through the National Team for the Acceleration of Poverty Reduction (TNP2K) is committed to eradicating extreme poverty, namely zero percent by the end of 2024. Based on the results of the 2021 TNP2K study, 5 districts/cities in Maluku were selected as priority areas for extreme poverty eradication in Indonesia. Therefore, the purpose of this study is to analyze the influence of household characteristics on extreme poverty status in Maluku in 2021. The results of the study using data from the March 2021 national socio-economic survey (Susenas) and the binary logistic regression analysis method show that at a significance level of 5 percent the number household members, building resilience, occupancy density, main source of lighting, and Non-Cash Food Assistance (BPNT) have a significant effect on the extreme poverty status of households in Maluku in 2021. In conclusion, to eradicate extreme poverty in Maluku, the government can prioritize improving the quality of facilities and supporting infrastructure for inter-island connectivity in Maluku, clove and nutmeg productivity development, industrialization of the fisheries sector through Lumbung Ikan Nasional (LIN) in Maluku, increased counseling on Keluarga Berencana (KB) program, KB villages, a livable housing program both from the aspect of building resilience and density housing, equitable access to electricity, and evaluating the list of beneficiaries of the BPNT program. For the sustainability of this research, regional variables such as village funds can be considered.